Features of cognitive functioning and functional disability in patients with traumatic encephalopathy - Дуве, Христина (Psychosomatic Medicine and General Practice, 2023)
Abstracts of the report "Peculiarities of cognitive functioning and functional disability in patients with traumatic encephalopathy"